2023
DOI: 10.1186/s12889-023-17177-3
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of lifestyle behaviours and analysis of their associations with MAFLD: a cross-sectional study of 196,515 individuals in China

Bingqian Zhou,
Ni Gong,
Qingnan He
et al.

Abstract: Background The aggregation of lifestyle behaviours and their association with metabolic-associated fatty liver disease (MAFLD) remain unclear. We identified lifestyle patterns and investigated their association with the risk of developing MAFLD in a sample of Chinese adults who underwent annual physical examinations. Methods Annual physical examination data of Chinese adults from January 2016 to December 2020 were used in this study. We created a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Based on analysis of approximately 200000 individuals in China, Zhou et al [ 11 ], found a significantly higher prevalence of MAFLD in men than in women (54.37% vs 20.88%). Additionally, fewer than 20% of men conducted a healthy lifestyle pattern as opposed to more than 90% of women[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on analysis of approximately 200000 individuals in China, Zhou et al [ 11 ], found a significantly higher prevalence of MAFLD in men than in women (54.37% vs 20.88%). Additionally, fewer than 20% of men conducted a healthy lifestyle pattern as opposed to more than 90% of women[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on analysis of approximately 200000 individuals in China, Zhou et al [ 11 ], found a significantly higher prevalence of MAFLD in men than in women (54.37% vs 20.88%). Additionally, fewer than 20% of men conducted a healthy lifestyle pattern as opposed to more than 90% of women[ 11 ]. This study confirms that NAFLD is more common among men than in pre-menopausal women and that, after menopause, women lose this “protection” from developing NAFLD[ 12 ].…”
Section: Introductionmentioning
confidence: 99%